Pengaruh Pemanfaatan Media Sosial Dan WA Bisnis Terhadap Loyalitas Pelanggan UMKM Di Jawa Timur - Andianto, M Mascun; Ridwan, Muhammad; Shalikha, Putri Ayu Anisatus (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This study examines the impact of social media and WA Business usage on the loyalty of MSME students in East Java using the Systematic Literature Review (SLR) technique. As the foundation of the Indonesian economy, MSMEs have difficulty in implementing digital technology to develop market share and grow consumer loyalty. Social media platforms such as Instagram and Facebook and Twitter offer opportunities to interact with customers and build brand awareness, while WA Business provides a more personal and responsive communication channel. Analysis of 20 relevant studies shows that social media is effective in increasing customer loyalty by strengthening relationships and engagement through relevant content. WA Business, on the other hand, increases satisfaction and loyalty through fast and personal communication. The synergy between social media and WA Business creates a more holistic customer experience, with social media attracting attention and WA Business providing deeper communication. Factors such as product type, customer demographics, and intensity of platform usage influence the effectiveness of this strategy. This study recommends that MSMEs integrate both platforms in their marketing strategies and adapt to digital trends to maintain competitiveness